Input from the frontlines: parole and probation officers' perceptions of policies directed at those convicted of sexual offenses. Issue 6 (2nd November 2022) - Kaylor, Leah; Feinberg, Michelle K.; Katsman, Kseniya; Allan, Cecilia; Greene-Colozzi, Emily; Johnson, Dylan; Jeglic, Elizabeth L.
Abstract : Sex offender laws were designed to decrease sexual violence. The current mixed methods study examined attitudes and opinions of parole and probation officers who have supervised individuals convicted of sexual offenses ( n  = 361) regarding sex offender legislation and how these policies can be most effective in preventing recidivism. About half of the officers reported that registration and notification, sexually violent predator and Halloween laws were largely effective in preventing sexual victimization. Conversely, they perceived residence restriction laws and the tier system to be largely ineffective. A consistent theme that emerged from the qualitative responses was a movement away from blanket approaches towards a case-specific approach, tailoring the laws to individuals based upon their needs and risk level.